2015
DOI: 10.1186/s12985-015-0385-2
|View full text |Cite
|
Sign up to set email alerts
|

Eastern equine encephalitis virus in mice II: pathogenesis is dependent on route of exposure

Abstract: BackgroundEastern equine encephalitis virus (EEEV) is an alphavirus with a case fatality rate estimated to be as high as 75 % in humans and 90 % in horses. Surviving patients often have long-lasting and severe neurological sequelae. At present, there is no licensed vaccine or therapeutic for EEEV infection. This study completes the clinical and pathological analysis of mice infected with a North American strain of EEEV by three different routes: aerosol, intranasal, and subcutaneous. Such an understanding is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…Within the CNS, neurons are the main target cells for encephalitic flaviviruses [154,170], alphaviruses [107,145], and members of the Bunyaviridae and Reoviridae [146,171,172]. Arboviral infection of other cell types of the CNS has also been reported (Table 2), and recent in vitro studies with ZIKV suggest it may target neural progenitor cells [173][174][175][176].…”
Section: Neuropathogenesis Of Arbovirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the CNS, neurons are the main target cells for encephalitic flaviviruses [154,170], alphaviruses [107,145], and members of the Bunyaviridae and Reoviridae [146,171,172]. Arboviral infection of other cell types of the CNS has also been reported (Table 2), and recent in vitro studies with ZIKV suggest it may target neural progenitor cells [173][174][175][176].…”
Section: Neuropathogenesis Of Arbovirusesmentioning
confidence: 99%
“…CNS invasion via olfactory bulb has been demonstrated for several encephalitic arboviruses, including SLEV [142], MVEV [143], VEEV [144], EEEV [145], and LACV [146]. Soon after onset of viremia, viral particles exit the fenestrated capillaries beneath the mucosa of the nasal cavity.…”
Section: Entry Of Arboviruses Into the Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…exposure of outbred CD-1 mice to WEEV.McM leads to virus entry into the CNS through the long axonal projections of olfactory sensory neurons (OSNs) (6,7) and supports other studies showing that VEEV and EEEV utilize OSNs as an important route of entry into the brain following i.n. or aerosol inoculation (8)(9)(10). Alphaviruses then disseminate in the CNS along the neuronal axis, with infection of the olfactory bulb glomerular layer and lateral olfactory tract being prominent features following i.n.…”
mentioning
confidence: 99%
“…Others have reported that s.c. injection of mice with VEEV leads to infection of the CNS through olfactory or peripheral nerves (12). A more recent study also supports the hypothesis that EEEV enters the CNS directly from blood following s.c. inoculation (9). However, the precise entry points of WEEV or EEEV in the brain remain to be determined.…”
mentioning
confidence: 99%